(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
India is presently going through phase of rapid urbanization due to enhanced economic growth specially at around urban centers leading to development of Urban agglomerate and multi-fold increase in number of vehicles plying in these cities, that is owing to transport related risk and crisis in these cities. Unplanned road network, deteriorating air quality, reduced areas under green space, no space for hawkers and pedestrian pathway, poor parking system are some of the risk transport sector as a result of rapid unplanned urbanization. It is estimated, that in 2007, the transport sector contributed emissions to the tune of 142.04 Mt CO2 eq in India alone. It accounted for approximately 13 of total energy related CO2 emissions (MoEF, 2010), of which majority of emissions were from the road transport. The Conditions in developing countries pose additional challenges on transportation systems – demand far exceeds supply, particularly for the growing number of urban poor getting pushed in urban center for better livelihood opportunity. Thus, to minimize this gap of demand and supply in transport sector an integration between land use and transportation system is mandatory to enhance resilience and ensuring sustainable planned urban development.